Implementation of Data-Driven Management in Improving Educational Quality: A Case Study at SDN Wangkalwetan, Kejayan District - Mustari, Eny; Harris, Taufiq; Wahyudi, M. Furqon; Rimadani, Eprilia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Data-driven management has become an essential approach in improving school quality amid increasing demands for accountability and evidence-based decision-making in education. However, empirical studies exploring how data-based management is implemented at the primary school level, particularly from a qualitative perspective, remain limited. This study aims to examine the implementation of data-driven management in improving educational quality at SDN Wangkalwetan, Kejayan District. Employing a qualitative case study design, data were collected through semi- structured interviews with the principal and teachers, participatory observations, and document analysis related to school planning and evaluation. The findings reveal that data-driven management at SDN Wangkalwetan is implemented through a cyclical process involving data identification, collaborative data interpretation, program planning, implementation, and evaluation. School performance data are primarily utilized to guide instructional supervision, teacher development programs, and learning improvement initiatives. Nevertheless, the study also identifies challenges related to teachers’ data literacy and limited infrastructural support. This research contributes theoretically by enriching the discourse on data-driven educational leadership in primary education contexts and practically by offering insights for school leaders and policymakers in strengthening evidence-based school management practices.